God, mystery & mystification - Turner, Denys, 1942- (University of Notre Dame Press, 2019)
"In God, Mystery, and Mystification, Denys Turner presents eight essays covering the major issues of philosophical and practical theology that he has focused on over the fifty years of his academic career. While a somewhat heterogeneous collection, the chapters are loosely linked by a focus on the mystery of God and on distinguishing that mystery from merely idolatrous mystifications. The book covers three main fields: theological epistemology, medieval and early modern mystical theologies, and the relation of Christian belief to natural science and politics. Turner develops the implications of a moderate realist account of theological knowledge as distinct from a fashionable, postmodernist epistemology. This modern realist epistemology is embodied in connections between theoretical, speculative theologies and the practice of the Christian faith in a number of different ways, but mainly as bearing upon the practical, lived connections between faith and reason, between reason and the mystical, between faith and science, and among faith, prayer, and politics. Scholars and advanced students of theology, religious studies, the history of ideas, and medieval thought will be interested in this book"--